ALTERATION IN LACTATE DEHYDROGENASE ACTIVITY IN COW MILK RELATED TO UDDER HEALTH STATUS - Vyavahare, S H; Bonde, S W; Mangle, N S; Ballamwar , V A; Waghmare , S P (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
An experiment was conducted to investigate the change in the activity of lactate dehydrogenase (EC 1.1.1.27) in the milk-whey and blood-plasma associated with udder health status of cows. A total of 60 quarter milk samples were collected on the basis of clinical examination of udder and California Mastitis Test (CMT) score, and grouped as normal, subclinical (1+, 2+, 3+) and clinical. The pH and somatic cell count (SCC) were determined in the whole milk and the lactate dehydrogenase (LDH) activity was estimated in the milk whey and blood-plasma, collected from the cows under study. The average values of pH and SCC in whole milk samples differ significantly among different udder health groups and revealed a direct relationship with CMT score and the LDH activity in milk-whey. The LDH activity in milk-whey differs significantly among different udder health status, however, it did not differ significantly in blood-plasma. The assay of LDH activity in milk-whey is therefore recommended to be useful parameter to assess the udder health status of the cows.
Keywords: CMT; SCC; LDH; Mastitis; Milk-whey